KUALITAS MIKROBIOLOGIS FILLET IKAN GABUS (Channa striata) DIAWETKAN DENGAN SUBSTRAT ANTIMIKROBA Pediococcus pentosaceus BAF715 SELAMA PENYIMPANAN SUHU CHILLING - Afriani Afriani (Jurnal Perikanan dan Kelautan, 2021)
Snakehead fish fillet is a perishable food product, caused by microbial activity. The way to overcome the damage is by preservation. Preservation using antimicrobial substrate from lactic acid bacteria is safe for health and inhibits the growth of rotting bacteria and pathogens in foodstuffs. This research has been carried out on the application of antimicrobial substrate from Pediococcus pentosaceus BAF715 preservation of fish fillets, stored at chilling temperatures. for 12 days. This study used a completely randomized design with 7 treatments and 3 replications and statistical analysis was carried out on the observed variables: pH, total bacteria, Escherichia coli, Staphilococcus aureus and Salmonella sp. The results of the analysis showed that after 8 days of storage there was an increase in pH, total microbes and S. aureus, but during storage there was no presence of E. coli and Salmonella. The microbiological quality of snakehead fish fillets preserved with antimicrobial substrate from Pediococcus pentosaceus BAF 715 stored at chilling temperature can be maintained for up to 8 days